Measuring the Impact on Farmers of Agricultural Radio and Television Programs in Southwest Nigeria - Mohammed Kuta Yahaya; Olabode ldris Badiru (Journal of Applied Communications, 2002)
In Nigeria, as in many other countries, limited numbers of extension agents (one to 4,000 farmers) make it impossible to reach all farmers by interpersonal means. For this reason, radio and, more recently, television have been used by agricultural organizations to disseminate relevant agricultural information to larger numbers of farm families at minimal cost and to areas hitherto not accessible to extension agents on a regular basis. While prior studies have confirmed that these radio programs have large audiences, there has been less attention to the perceptions farmers hold about the specific benefits these programs proVide. The purpose of this study was to examine the performance of two long-running Nigerian agricultural programs, one for radio and the second for TV, as perceived by 198 randomly selected farmers in Oyo State of southwest Nigeria. Results indicate a very positive assessment of both specific program components and the value of the two programs for improving agricultural production across 12 perceptual dimensions.